nCODET: A Tool For Novice Developer To Detect Untestable Code - et.al, Saiful Bahri Hisamudin (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Uncontrollability is troublesome for unit testing. It causes a non-deterministic behavior where the same input can produce different results based on different executions. The non-deterministic characteristic makes it impossible to test the internal logic of a method because it suffers from tight coupling, a single responsibility principle violation, being an untestable code, being non-reusable or hard to maintain. This paper describes a tool, namely the non-deterministic Code Detection Tool (nCODET) that aims to assist novice developers to write testable codes by avoiding the non-deterministic characteristic in their codes. Our research focuses on the unit testability of classes; particularly the effort involvedin constructing unit test cases.